Effect of Heat Transfer on Wall Thickness and Insulation at Sterilizer Station PT. Socfindo Kebun Seunagan - M. Fahrul Rozi Abdus samad; Sulaiman Ali (Jurnal Inotera, 2022)
Palm Oil Mill PT. Socfindo Kebun Seunagan is a factory engaged in the processing of palm oil, which is obtained in Crude Oil or called Crude Palm Oil (CPO) and Kernel Oil. PT. Socfindo Kebun Seunagan has also experienced a conflict in the Sterilizer machine, which is a very important machine for processing Crude Oil. Stabilizer at PT. Socfindo Kebun Seunagan uses 3 horizontally shaped boiling units, each with a capacity of 7 lorries, each lorry containing two, five tons. A sterilizer means a pressure vessel used to cover palm oil, which uses steam as a heating medium that comes from a back pressure vessel that has a pressure of 2.0 bar and a temperature of 100 C. If the above requirements are not met, then the CPO production efficiency obtained may not be able to meet the specified specifications. therefore this analysis needs to be done so that we can understand or find out how to analyze heat transfer in the Sterilizer machine at PT. Socfindo Seunagan Gardens. This allows us to know the incoming energy, outgoing power, heat efficiency, losses, and changes in energy in transient conduction. The energy that comes out of each peak is Peak I as much as 48979,614 kJ, peak II at 79169,164 kJ and at Peak III as much as 81705,414 kJ. The highest heat efficiency is found in peak I of 0.846277. the lowest losses are at peak III as much as 51.765kJ.